2017
DOI: 10.1589/jpts.29.970
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effect of diaphragm taping with breathing exercise on muscle tone and stiffness of respiratory muscles and SpO<sub>2</sub> in stroke patient

Abstract: [Purpose] This study aimed to examine the immediate effects of diaphragm taping with breathing exercise on the tone and stiffness in the respiratory muscles of patient with stroke. [Subjects and Methods] A total of 28 subjects, 14 in the diaphragm taping with breathing exercise group and 14 in the breathing exercise group, were administered respective intervention methods. Subsequently, the muscle tone and stiffness in upper trapezius, scalene, external oblique abdominal and ractus abdominis muscle of both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
9
0
4
Order By: Relevance
“…According to Wang et al 11 ) , the increase in muscle tone and stiffness of respiratory muscles among paralyzed patients following respiration exercises was a positive change in their respiratory muscles. Park 4 ) showed that there was an increase in chest expansion and respiratory muscle activity when rib cage joint mobilization was applied to stroke patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wang et al 11 ) , the increase in muscle tone and stiffness of respiratory muscles among paralyzed patients following respiration exercises was a positive change in their respiratory muscles. Park 4 ) showed that there was an increase in chest expansion and respiratory muscle activity when rib cage joint mobilization was applied to stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects showed asymmetry in respiratory muscle tone and stiffness 11 ) . In this present study, the subjects showed a significant increase in the tone and stiffness of SCM, EO, UT, and LD compared with the injured side before the intervention took place.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, while applying cervical joint mobilization, the patient was asked to maintain awareness of their respiration. The recognition of respiration in this study is noteworthy in that it used diaphragmatic breathing [ 38 ]. The phrenic nerve is located at C3-C4 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The descending fiber of the trapezius muscle was chosen because it was related to the biomechanical alignment of the face and neck and, therefore, it contributes to the various functions of the stomatognathic and respiratory systems (14,15,25) .…”
Section: Discussionmentioning
confidence: 99%
“…The tape was bilaterally applied on the descending fibers of the trapezius muscle. This muscle was chosen because of its relationship with the biomechanical alignment of the face and neck, which contributes to the various functions of the stomatognathic system and respiration (14,15) .…”
Section: Methodsmentioning
confidence: 99%